A Systematic Review of the English Situation in the Implementation of the ASEAN Economic Community (AEC) - Fauzanna, Wulan (Vivid: Journal of Language and Literature, 2023)
The implementation of the ASEAN Economic Community (ACE) in the ASEAN countries also has several possible impacts on the increasing use of English in the ASEAN countries especially on teaching and learning English in education system. In addition, to identify the skills to fullfill the requirement to work across ASEAN. There is a need to identify the need for the current study on the situation of English in ASEAN during the AEC implementation with the systematic review analysis. This systematic review was guided by the PRISMA statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) in its systematic online database searching involving keyword searching, inclusion, and exclusion criteria. The results show the methods that have been used include qualitative, quantitative amd also mixed methods. In addition, five main themes are identified; English for ASEAN regionalism, English skills for working in ASEAN, English as lingua franca in ASEAN, English in the curriculum, and English in the education system. Based on this analysis the review identified the recommendation for English teaching.